Sanghuangporus sanghuang Mycelium Prevents Paracetamol-Induced Hepatotoxicity through Regulating the MAPK/NF-κB, Keap1/Nrf2/HO-1, TLR4/PI3K/Akt, and CaMKKβ/LKB1/AMPK Pathways and Suppressing Oxidative Stress and Inflammation - Wen-Ping Jiang; Jeng-Shyan Deng; Shyh-Shyun Huang; Sheng-Hua Wu; Chin-Chu Chen; Jung-Chun Liao; Hung-Yi Chen; Hui-Yi Lin; Guan-Jhong Huang (MDPI AG, 2021)
Liver damage induced by paracetamol overdose is the main cause of acute liver failure worldwide. In order to study the hepatoprotective effect of Sanghuangporus sanghuang mycelium (SS) on paracetamol-induced liver injury, SS was administered orally every day for 6 days in mice before paracetamol treatment. SS decreased serum aminotransferase activities and the lipid profiles, protecting against paracetamol hepatotoxicity in mice. Furthermore, SS inhibited the lipid peroxidation marker malondialdehyde (MDA), hepatic cytochrome P450 2E1 (CYP2E1), and the histopathological changes in the liver and decreased inflammatory activity by inhibiting the production of proinflammatory cytokines in paracetamol-induced acute liver failure. Moreover, SS improved the levels of glutathione (GSH), superoxide dismutase (SOD), glutathione peroxidase (GPx), and catalase in the liver. Significantly, SS diminished mitogen-activated protein kinase (MAPK), Toll-like receptor 4 (TLR4), phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt), and the nuclear factor-kappa B (NF-κB) axis, as well as upregulated the Kelch-like ECH-associated protein 1 (Keap1)/erythroid 2-related factor 2 (Nrf2)/heme oxygenase-1 (HO-1) pathway, in paracetamol-induced mice. SS mainly inhibited the phosphorylation of the liver kinase B1 (LKB1), Ca2+/calmodulin-dependent kinase kinase β (CaMKKβ), and AMP-activated protein kinase (AMPK) protein expression. Furthermore, the protective effects of SS on paracetamol-induced hepatotoxicity were abolished by compound C, an AMPK inhibitor. In summary, we provide novel molecular evidence that SS protects liver cells from paracetamol-induced hepatotoxicity by inhibiting oxidative stress and inflammation.